PEMAKAIAN TEORI KEMASYARAKATAN IBN KHALDUN DALAM MEMPERKAYA KONSEPSI KURATOR MUSEUM ISLAM - Ahmad Farid Abdul Jalal; Rahimin Affandi Abdul Rahim (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2019)
This article discusses the importance of museum curators for developing civilization. The magnitude of the concept of the museum curator can be derived from the theory of Ibn Khaldun. With literature review, this study found that the theory of Sociology-History theory proposed by Ibn Khaldun could be utilized for the profession of the museum's curator. It's not just about improving the curators in their day-to-day tasks, but also empowering them to make them more critical in handling issues. The application of Ibn Khaldun's theory may be an alternative to the rise of the Malay knowledge system as a nation that must have been excluded from colonialism, including in geopolitical and science (epistemology).